Downregulation of miR-224-5p Promotes Migration and Proliferation in Human Dental Pulp Stem Cells - Ke, Zhihong (Biomed Res Int, 2019)
INTRODUCTION: Pulp regeneration, as a treatment for pulp necrosis, has significant advantages over root canal therapy for the preservation of living pulp. To date, research on pulp regeneration has mainly focused on the transplantation of pulp stem cells into the root canal, but there is still a lack of research on the migration of pulp cells into the root canal via cell homing. Stem cells from the apical tooth papilla (SCAP) are recognized as multidirectional stem cells, but these cells are difficult to obtain. MicroRNAs are small noncoding RNAs that play crucial roles in regulating normal and pathologic functions. We hypothesized that some types of microRNAs might improve the migration and proliferation function of dental pulp stem cells (DPSCs), which are easily obtained in clinical practice, and as a result, DPSCs might replace SCAP and provide valuable information for regenerative endodontics. METHODS: Magnetic activated cell sorting of DPSCs and SCAP was performed. Next-generation sequencing was performed to examine DPSCs and SCAP miRNAs expression and to identify the most significant differentially expressed miRNA. CCK-8 and transwell assays were used to determine the impact of this miRNA on DPSCs proliferation and migration. RESULTS: The most significant differentially expressed miRNA between DPSCs and SCAP was miR-224-5p. Downregulating miR-224-5p promoted DPSCs proliferation and migration; the opposite results were observed when miR-224-5p was upregulated. CONCLUSION: MiR-224-5p promotes proliferation and migration in DPSCs, a finding that is of great significance for further exploring the role of dental pulp stem cells in regenerative endodontics.